Granisetron and Ondansetron on Post Operative Nausea and Vomiting in Laparoscopic Cholecystectomy Under General Anesthesia At Bir Hospital Kathmandu, Nepal - Bhattarai, Ramesh; Vaidya, P R; Chand, M B (Birat Journal of Health Sciences, 2017)
IntroductionLaparoscopic cholecystectomy has higher incidence of postoperative nausea and vomiting (PONV). In routine practice single dose of drug is given prophylactically during the surgery.ObjectiveThis study aimed to compare the antiemetic efficacy of two different 5-hydroxytryptamine-3 (5HT3) receptor antagonists, Ondansetron and Granisetron when given prophylactically to patients undergoing laparoscopic cholecystectomy.MethodologyIt was a randomized, single blind study, conducted in 75 patients undergoing laparoscopic cholecystectomy. Patients were divided into two groups: Group O and Group G. Patients in group O were given 0.1 mg/kg Ondansetron intravenously (IV) and patients in Group G were given 0.04 mg/kg Granisetron. The standard general anesthetic technique was administered to all the patients. Episodes of nausea, retching and vomiting were assessed during the first 24 hours after  anesthesia. Collected data was applied with appropriate test in SPSS 16 and overall significance level was considered at 95% confidence interval (p ≤ 0.05).ResultsThere was no statistically significant difference for demographic data among the two groups (P>0.05). Both drugs were similarly effective in first four hours (P>0.05). Between 4–12 hours and 12-24 hours, episodes of nausea and vomiting were higher in Ondansetron group.ConclusionThe incidence of PONV was significantly high in Ondansetron than in Granisetron given prophylactically in laparoscopic cholecystectomy. Birat Journal of Health SciencesVol.2/No.1/Issue 2/ Jan - April 2017, page: 175-178